The Role of Zakat in Reducing Poverty in Rural Communities of Pandeglang Regency - Safera, Nurul; Erdi Rujikartawi; Yusaro Hasnee (TSARWAH, 2025)
This study explores the role of zakat in reducing poverty in rural areas, particularly in Pandeglang Regency, where socioeconomic disparities remain prominent. Despite its potential to improve community welfare, the actual impact of zakat on poverty alleviation in rural contexts is still underexplored. This research aims to identify the contribution of zakat in enhancing the quality of life for the poor and examine the factors that support or hinder zakat program implementation. A qualitative method was used, involving four purposively selected informants: an amil, a muzakki, and two mustahik. Data were collected through in-depth interviews and analyzed thematically. The study adopts the Theory of Community Empowerment and the Maqashid Shariah framework to interpret the findings. Results show that zakat contributes positively to basic needs fulfillment and temporary financial relief. However, challenges such as limited program resources, uneven distribution, lack of monitoring, and beneficiary dependence reduce long-term effectiveness. The study concludes that improving zakat management, professionalizing amil roles, enhancing public outreach, and integrating technology for transparency are crucial for maximizing impact. The research offers theoretical and practical implications, and suggests further exploration of zakat’s synergy with digital-based rural development programs.